2012
DOI: 10.1111/j.1476-5381.2012.01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial β2‐adrenoceptor gene delivery promotes coordinated cardiac adaptive remodelling and angiogenesis in heart failure

Abstract: BACKGROUND AND PURPOSEWe investigated whether b2-adrenoceptor overexpression could promote angiogenesis and improve blood perfusion and left ventricular (LV) remodeling of the failing heart. EXPERIMENTAL APPROACHWe explored the angiogenic effects of b2-adrenoceptor overexpression in a rat model of post-myocardial infarction (MI) heart failure (HF). Cardiac adenoviral-mediated b2-adrenoceptor overexpression was obtained via direct intramyocardial injection 4-weeks post-MI. Adenovirus(Ad)-GFP and saline injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Previously, we have shown that exercise training, independently from HRR, is able to induce VEGF upregulation and Akt activation in the post-ischemic heart (22) and to improve age-dependent VEGF downregulation and angiogenesis responses to hindlimb ischemia (26). Moreover, 2AR overexpression in the failing heart is able to enhance neoangiogenesis inducing a sustained and coordinated Akt and VEGF activation (21). The involvement of 2AR in the neoangiogenic processes in response to ischemia prompted us to use in this study a selective 1AR blocker, in order to not interfere with 2AR.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, we have shown that exercise training, independently from HRR, is able to induce VEGF upregulation and Akt activation in the post-ischemic heart (22) and to improve age-dependent VEGF downregulation and angiogenesis responses to hindlimb ischemia (26). Moreover, 2AR overexpression in the failing heart is able to enhance neoangiogenesis inducing a sustained and coordinated Akt and VEGF activation (21). The involvement of 2AR in the neoangiogenic processes in response to ischemia prompted us to use in this study a selective 1AR blocker, in order to not interfere with 2AR.…”
Section: Discussionmentioning
confidence: 93%
“…At the molecular level, it is known that the b 2 -adrenergic receptor (b 2 AR), the most abundant b adrenergic receptor (bAR) isoform in ECs, is involved in the control of these functions (Howell et al, 1988). However, ischemia can result in increased sympathetic catecholamine levels that can cause b 2 AR signaling dysfunction in ECs, resulting in an inadequate angiogenic response and loss of tissue integrity and/or function (Iaccarino et al, 2005;Rengo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although a more exhaustive evaluation of all neurohormonal activation indexes (i.e. plasma norephinephrine, components of the renin-angiotensin system) [38] are lacking, NT-proBNP is widely recognized as a key component of neurohormonal activation pattern [39]. Despite the afore mentioned limitations, this study has several unique strengths.…”
Section: Discussionmentioning
confidence: 99%